Predictors of Instructors’ Teaching Performance: Basis for Online Teaching Enhancement (Universitas Negeri Semarang, 2021)
The instructors’ teaching skills and satisfaction are vital in their online teaching performance. This study determined the college instructors’ online teaching skills and satisfaction in relation to their teaching performance. This study utilized a descriptive-correlational design. One hundred twenty-one college instructors were chosen as respondents through random sampling. The researchers used frequency, Percentage, Mean, Standard Deviation, Pearson Product Moment Correlation Coefficient and Stepwise Multiple Regression Analysis in analyzing the data. Results showed that instructors had excellent teaching skills, a very high level of job satisfaction, and very satisfactory teaching performance in online classes. Social and communication skills in teaching and the support that the instructors received from the institution were the predictors of their online teaching performance. Administrators may extend support to the instructors with training and workshops and give rewards and incentives for those outstanding faculty to enhance their satisfaction and encourage others to perform better in online teaching. Abstrak Keterampilan mengajar dan kepuasan dari instruktur penting dalam kinerja pembelajaran online mereka. Penelitian ini menelaah keterampilan instruktur kampus dalam mengajar online dan kepuasan terkait dengan kinerja mengajar mereka. Penelitian ini menggunakan desain deskriptif-korelasional, sebanyak 121 instruktur kampus dipilih sebagai responden menggunakan teknik sampling acak. Peneliti menggunakan frekuensi, persentase, rata-rata, standar deviasi, teori koefisien korelasi produk momen dari Pearson, dan analisis multiple regresi dari Stepwise untuk analisis data. Hasil penelitian menunjukkan bahwa para instruktur telah memiliki keterampilan mengajar yang luar biasa dengan tingkat kepuasan kerja yang sangat tinggi dan juga menunjukkan kinerja mengajar kelas-kelas online yang sangat memuaskan. Keterampilan sosial dan komunikasi dalam mengajar dan dukungan yang diterima oleh para instruktur dari Lembaga menjadi predictor dari kinerja pengajaran online mereka. Tenaga administrasi juga menjadi faktor pendukung para instruktur melalui pelatihan dan lokakarya serta pemberian hadiah dan insentif bagi fakultas yang telah menunjukkan kinerja luar biasa untuk meningkatkan tingkat kepuasan dan mendorong fakultas lain untuk juga meningkatkan kinerjanya dalam pengajaran online.